Primary-care-based social prescribing for mental health: an analysis of financial and environmental sustainability. Issue 2 (29th May 2015) - Maughan, Daniel L.; Patel, Alisha; Parveen, Tahmina; Braithwaite, Isobel; Cook, Jonathan; Lillywhite, Rob; Cooke, Matthew
Abstract : Aim: To assess the effects of a social prescribing service development on healthcare use and the subsequent economic and environmental costs. Background: Social prescribing services for mental healthcare create links with support in the community for people using primary care. Social prescribing services may reduce future healthcare use, and therefore reduce the financial and environmental costs of healthcare, by providing structured psychosocial support. The National Health Service (NHS) is required to reduce its carbon footprint by 80% by 2050 according to the Climate Change Act (2008). This study is the first of its kind to analyse both the financial and environmental impacts associated with healthcare use following social prescribing. The value of this observational study lies in its novel methodology of analysing the carbon footprint of a service at the primary-care level. Method: An observational study was carried out to assess the impact of the service on the financial and environmental impacts of healthcare use. GP appointments, psychotropic medications and secondary-care referrals were measured. Findings: Results demonstrate no statistical difference in the financial and carbon costs of healthcare use between groups. Social prescribing showed a trend towards reduced healthcare use, mainly due to a reduction in secondary-care referrals compared with controls. The associations found did not achieve significance due to the small sample size leading to a large degree of uncertainty regarding differences. This study demonstrates that these services are potentially able to pay for themselves through reducing future healthcare costs and are effective, low-carbon interventions, when compared with cognitive behavioral therapy or antidepressants. This is an important finding in light of Government targets for the NHS to reduce its carbon footprint by 80% by 2050. Larger studies are required to investigate the potentials of social prescribing services further.